2021
DOI: 10.1038/s41366-021-00968-2
|View full text |Cite
|
Sign up to set email alerts
|

Age- and weight group-specific weight gain patterns in children and adolescents during the 15 years before and during the COVID-19 pandemic

Abstract: Background/Objectives There is a concern that measures aiming to limit a further spread of COVID-19, e.g., school closures and social distancing, cause an aggravation of the childhood obesity epidemic. Therefore, we compared BMI trends during the 15 years before and during the COVID-19 pandemic. Subjects/Methods To assess the change in weight dynamics during the first months of COVID-19, we compared the trends of 3-month change in BMI-SDS (ΔBMI-SDS) and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
2
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 53 publications
(69 reference statements)
7
71
2
9
Order By: Relevance
“…Specifically, 28.9% of boys were over the cut point prepandemic, and this value increased to 34.6% in pandemic, whereas girls presented similar values prepandemic (25.8%) and during the pandemic (27.2%) ( Figure 6 ). COVID-19 lockdown and subsequent restriction have had a relevant effect on habits [ 36 , 37 ] and physical activity levels [ 28 , 38 ], influencing the weight gain and adiposity increases detected in this population during pandemic [ 25 , 36 , 39 ]. Although it has been reported that upon return to school after lockdown, levels of physical activity increased in both sexes but especially in boys [ 38 ], our data would suggest that this increase in physical activity would not be sufficient to fully counteract the effect of some sedentary habits on the body composition of the male school population.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, 28.9% of boys were over the cut point prepandemic, and this value increased to 34.6% in pandemic, whereas girls presented similar values prepandemic (25.8%) and during the pandemic (27.2%) ( Figure 6 ). COVID-19 lockdown and subsequent restriction have had a relevant effect on habits [ 36 , 37 ] and physical activity levels [ 28 , 38 ], influencing the weight gain and adiposity increases detected in this population during pandemic [ 25 , 36 , 39 ]. Although it has been reported that upon return to school after lockdown, levels of physical activity increased in both sexes but especially in boys [ 38 ], our data would suggest that this increase in physical activity would not be sufficient to fully counteract the effect of some sedentary habits on the body composition of the male school population.…”
Section: Discussionmentioning
confidence: 99%
“…ausgeführt [23]. Eine genauere Darstellung der statistischen Methoden ist in der Originalpublikation zu finden [24]. Während der Pandemie war der stärkste Anstieg der Gewichtszunahme bei jüngeren Kindern zu verzeichnen, während bei Jugendlichen die Adipositas vor der Pandemie am ausgeprägtesten war.…”
Section: Statistische Methodenunclassified
“…Moreover, numerous reports have suggested that unhealthy weight gain frequently occurred during the lockdown imposed by the COVID-19 pandemic [ 35 , 36 , 37 ]. Several authors have speculated that, compared with the pre-pandemic period, both BMI-z-scores, and childhood obesity prevalence under COVID-19 would rise, and the magnitude of the increase would be proportional to the length and severity of the pandemic [ 38 , 39 ]. Recently, Vogel et al compared the trends of BMI changes and the proportions of high positive (HPC)/negative weight changes (HNC) from 2005 to 2019 with the respective changes from 2019 (pre-pandemic) to 2020 (after the onset of anti-pandemic measures) in a large pediatric cohort in Germany.…”
Section: Epidemiology Of Pediatric Obesity and Its Major Risk Factorsmentioning
confidence: 99%
“…Thus, in this recent study reported data have significantly supported the dramatic effects of pandemic on the still-growing problem of childhood obesity. In fact, these effects increased by more than 30 times within a relatively short period, suggesting that changes in health-related behavior lead to a significant further aggravation of the childhood obesity pandemic [ 39 ]. Moreover, Shlomit et al, in a retrospective cohort study, analyzed changes in BMI among a large Israel population of children, adolescents and young adults during the COVID-19 pandemic in Israel.…”
Section: Epidemiology Of Pediatric Obesity and Its Major Risk Factorsmentioning
confidence: 99%